PENGARUH METODE PEMUASAAN TERHADAP PERTUMBUHAN LOBSTER AIR TAWAR (Cherax quadricarinatus) - ., Suwarsito; Nugroho, Didik Trianto; Mulia, Dini Siswani (Universitas Muhammadiyah Purwokerto, 2007)
The aim of research were to know effect of fasting method on growth of aquatic crayfish (Cherax quadricarinatus) and feed efficiency. The experiment used Completely Randomized Design (CRD), consist of 4 treatments and 3 replicates. The treatments were P1 (aquatic crayfish were fed one day and fasted one day), P2 (aquatic crayfish were fasted every Monday and Thursday), P3 (aquatic crayfish were fed two days and fasted two days), and P4 (aquatic crayfish were fed everyday/control). Aquatic crayfish with initial average body weight of 5 g used in this experiment. Aquatic crayfish were cultivated in cement pond (100 x 60 x 50 cm3) with density 20 crayfishes/pond for 40 days. Aquatic crayfish were fed at 5% of body weight. Results of research indicate that fasting method had effect on growth of aquatic crayfish and feed efficiency, but had no effect on survival rate of aquatic crayfish. Treatment P1 showed highest growth of aquatic crayfish and feed efficiency.